(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2015)
In the context of Partition, two competing hypotheses for Partitionethnic cleansing can be examined: whether the ethnic cleansing was largelyappropriative to cleanse the minority to seize either their goods or todisplace them from lucrative economic roles that would benefit privateindividuals or whether ethnic cleansing served a purpose to reduce economiccompetition for a group or to ensure the majority’s control of politics. We have chosen to focus our empirical analysis on religioushomogenization, minority and co-religionist majority knows, as we feel theseare good gauges of the processes of ethnic cleansing that took place during thePartition of India. Yet a natural question that remains is whether the patternsof ethnic cleansing actually also reacts the violence that took place duringthe Partition as well.